Withholding or withdrawing life-sustaining treatment in extremely low gestational age neonates. Issue 3 (20th October 2020) - Dworetz, April R; Natarajan, Girija; Langer, John; Kinlaw, Kathy; James, Jennifer R; Bidegain, Margarita; Das, Abhik; Poindexter, Brenda; Bell, Edward F; Cotten, C M; Kirpalani, Haresh; Shankaran, Seetha; et al.
Abstract : Objective: To identify sociodemographic and clinical factors associated with withholding or withdrawing life-sustaining treatment (WWLST) for extremely low gestational age neonates. Design: Observational study of prospectively collected registry data from 19 National Institute of Child Health and Human Development Neonatal Research Network centres on neonates born at 22–28 weeks gestation who died >12 hours through 120 days of age during 2011–2016. Sociodemographic and clinical factors were compared between infants who died following WWLST and without WWLST. Results: Of 1168 deaths, 67.1% occurred following WWLST. Withdrawal of assisted ventilation (97.4%) was the primary modality. WWLST rates were inversely proportional to gestational age. Life-sustaining treatment was withheld or withdrawn more often for non-Hispanic white infants than for non-Hispanic black infants (72.7% vs 60.4%; 95% CI 1.00 to 1.92) or Hispanic infants (72.7% vs 67.2%; 95% CI 1.32 to 3.72). WWLST rates varied across centres (38.6–92.6%; p<0.001). The centre with the highest rate had adjusted odds 4.89 times greater than the average (95% CI 1.18 to 20.18). The adjusted odds of WWLST were higher for infants with necrotiing enterocolitis (OR 1.77, 95% CI 1.21 to 2.59) and severe brain injury (OR 1.98, 95% CI 1.44 to 2.74). Conclusions: Among infants who died, WWLST rates varied widely across centres and were associated with gestational age, race, ethnicity, necrotiing enterocolitis, and severe brain injury. Further exploration is needed into how race, centre, and approaches to care of infants with necrotiing enterocolitis and severe brain injury influence WWLST.